Repenser l’intégration républicaine à l’aune de l’interculturalité - Alexander Frame (Communiquer)
This article analyses the French system of “republican integration” and emphasizes the potential contribution of an intercultural approach to inform and accompany public policy reforms currently taking place in this domain. Companies spend a lot of money on training for expatriate managers, while tens of thousands of other migrants, often alienated from society, do not have the benefit of such cultural awareness training. In the light of a recent parliamentary white paper on the integration of migrants (February 2018), different paradigms—value-based, social constructionist or critical—are used to highlight the current logic and underlying social dynamics of the republican integration system. Based on a local study of institutional bodies and voluntary-sector activity involving migrant integration in the greater-Dijon area, this article outlines ways to improve integration through cultural awareness training for migrants and other stakeholders.